Different effects of attachment anxiety and attachment avoidance on depressive symptoms: A meta-analysis. (December 2020) - Zheng, Leying; Luo, Yadan; Chen, Xu
Although insecure adult attachment is thought to be associated with depressive symptoms, results of research on the link between attachment dimensions (attachment anxiety and attachment avoidance) and depressive symptoms have been inconsistent. The aim of this study was to use meta-analysis to examine the strength of the correlations between the two attachment dimensions and depressive symptoms. A total of 64 papers and 78 independent samples were included in this meta-analysis. Results showed significant associations between both attachment dimensions and depressive symptoms. Additional analyses indicated that attachment anxiety was more strongly related to depressive symptoms, whereas attachment avoidance was weakly related to depressive symptoms. Cultural orientation and sex were found to moderate the relationship between attachment anxiety and depressive symptoms. Age was a significant moderator of the relationships between both attachment anxiety and avoidance and depressive symptoms. Results of the meta-analysis and the implications were discussed.